2018
DOI: 10.1016/j.jhsa.2018.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Avascular Necrosis of the Metacarpal Head: A Review of 4 Cases

Abstract: Therapeutic V.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(37 citation statements)
references
References 9 publications
1
33
0
3
Order By: Relevance
“…Some studies have also reported its association with trauma and anatomic variations in the blood supply to the metacarpal head. [ 2 , 3 , 7 ] Adolescents make up a large proportion of the cases, with more than 50% of the reported patients being under the age of 20. [ 3 ] In addition to individuals with definite steroid use, most of the patients have a history of trauma.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Some studies have also reported its association with trauma and anatomic variations in the blood supply to the metacarpal head. [ 2 , 3 , 7 ] Adolescents make up a large proportion of the cases, with more than 50% of the reported patients being under the age of 20. [ 3 ] In addition to individuals with definite steroid use, most of the patients have a history of trauma.…”
Section: Discussionmentioning
confidence: 99%
“…[ 2 , 3 , 7 ] Adolescents make up a large proportion of the cases, with more than 50% of the reported patients being under the age of 20. [ 3 ] In addition to individuals with definite steroid use, most of the patients have a history of trauma. [ 3 , 7 , 18 , 19 ]…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations